METHODOLOGY FOR EFFECTIVE CONTROL OF KNOWLEDGE, SKILLS AND COMPETENCIES OF CADETS IN PRACTICAL CLASSES IN HIGHER MATH (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article provides an example of the methodology for conducting current, intermediate and final types of control of the effective control of knowledge and practical skills of cadets in practical classes in higher math.